Brand and packaging of Pga K’nyau ethnic handicraft products for Pga K’nyau Ban Pa Ngio Community - Orkaew, Pattarakorn (Journal of Fine and Applied Arts Khon Kaen University, 2024)
This research aims to; 1) Study and collect data of woven fabric products for Pga K’nyau Ban Pa Ngio Community 2) Develop brand and packaging for Pga K’nyau woven fabrics Ban Pa Ngio Community and 3) Evaluate satisfaction to woven fabric products packaging for Pga K’nyau Ban Pa Ngio Community. Collecting data from 3 groups; The first were 10 entrepreneurs who are members of the group is a purposive sampling that uses an in-depth interview the second group consisted of 3 design experts using a scaled questionnaire. (Rating Scale) and the third group were 90 consumers who buy ethnic Pga K’nyau weaving fabrics by simple random sampling using a questionnaire. The results showed that woven fabric products were the way of the Pga K’nyau villagers who have been taught by their ancestors. The most customers reason for purchasing are beauty, uniqueness, and practical products. The results of brand design that called Yupoh in Pga K’nyau language means Bombax ceiba Linn or Red cotton tree flowers. The result of packaging design shows that the packaging structure is made from kraft paper (KP). It is a hexagonal box with the pack product from the bottom of the box. In addition, the structure has a function that can extend the hanging ears from the box to display the product at the point of sale. The graphics on the packaging use only one color is red color comes from red cotton tree flowers which the flower of the Pa Ngio Community. The graphic pattern indicates the uniqueness of the woven fabric for Pga K’nyau. The pattern unfolded by embroidery with colorful threads and millet embroidery on a woven cloth called "Ker Pomae" means spider’s teeth. The satisfaction assessment results of the target group to the brand is high level ( = 3.89, SD. = 0.88). The satisfaction to the woven fabric packaging prototype is high level ( = 4.43, SD. = 0.71).